2018
DOI: 10.1515/fon-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of formula feeding their infants: an interpretative phenomenological study

Abstract: Objective This study aimed to explore the experiences of women in the process of formula feeding their infants. The World Health Organization has emphasized the importance of breastfeeding for infant health. After decades of breastfeeding promotions, breastfeeding rates in Hong Kong have been rising consistently; however, the low continuation rate is alarming. This study explores women’s experiences with formula feeding their infants, including factors affecting their decision to do so. Methods A qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(58 reference statements)
0
1
0
1
Order By: Relevance
“…This study is consistent with the studies done in Dire Dawa and Hong Kong. 27,44 A study in Hong Kong Kong found women to be more likely to initiate discussions about infant feeding with family and friends because healthcare providers perceived them as not being supportive of formula feeding. Advice from friends, neighbors, and family heavily influenced the initiation of infant formula feeding.…”
mentioning
confidence: 99%
“…This study is consistent with the studies done in Dire Dawa and Hong Kong. 27,44 A study in Hong Kong Kong found women to be more likely to initiate discussions about infant feeding with family and friends because healthcare providers perceived them as not being supportive of formula feeding. Advice from friends, neighbors, and family heavily influenced the initiation of infant formula feeding.…”
mentioning
confidence: 99%
“…Однако исследование показало, что матери игнорировали неудобства кормления смесью, например, такие как мытье бутылочки для кормления, стоимость смеси, особенно некоторых из наиболее известных брендов и т. п. [10,11].…”
Section: Introductionunclassified
“…Finding ways to increase mothers' level of interest in and enthusiasm for the practice would be useful because mothers with a genuine interest in it are relatively more committed to the practice and more satisfied with better psychological well-being. 36,[49][50][51]…”
Section: Introductionmentioning
confidence: 99%